2009
DOI: 10.1007/s00393-009-0441-7
|View full text |Cite
|
Sign up to set email alerts
|

Zur Differenzialindikation anatomischer und inverser Schulterendoprothesen bei chronischer Polyarthritis

Abstract: The results of anatomical prostheses depend substantially on the extent of damage to the rotator cuff. Implantation of a semi-constrained inversed prosthesis provides a solution for severely damaged joints since it has a fixed centre of rotation. One prerequisite of success, however, is a sufficient bone stock in the glenoid region. The indication for bipolar prostheses, in contrast, is particularly strong when implantation of an inverse prosthesis is no longer possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In 19 reporting on patients who had undergone RSA or TSA, there were no rheumatoid patients with RSA [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]; nine studies on patients who had had an RSA for various aetiologies included one or more rheumatoid patients, but no or insufficient information was provided on their outcomes [26][27][28][29][30][31][32][33][34]; three review articles on RSA in patients with various conditions gave very little information, contained in a short paragraph [35,36], or limited information [37], for the RA group; there were also two articles of general information on shoulder arthroplasty reporting no own case series [38,39]. Two additional studies reported enough pertinent and useful information on several [40] or many [41] RA patients undergoing RSA, but they were excluded because the mean follow-up was less than 36 months and the longest did not reach five years. This review was thus based on the five studies that met the inclusion criteria [42][43][44][45][46]: all dealing exclusively with RA patients.…”
Section: Study Selectionmentioning
confidence: 99%
“…In 19 reporting on patients who had undergone RSA or TSA, there were no rheumatoid patients with RSA [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]; nine studies on patients who had had an RSA for various aetiologies included one or more rheumatoid patients, but no or insufficient information was provided on their outcomes [26][27][28][29][30][31][32][33][34]; three review articles on RSA in patients with various conditions gave very little information, contained in a short paragraph [35,36], or limited information [37], for the RA group; there were also two articles of general information on shoulder arthroplasty reporting no own case series [38,39]. Two additional studies reported enough pertinent and useful information on several [40] or many [41] RA patients undergoing RSA, but they were excluded because the mean follow-up was less than 36 months and the longest did not reach five years. This review was thus based on the five studies that met the inclusion criteria [42][43][44][45][46]: all dealing exclusively with RA patients.…”
Section: Study Selectionmentioning
confidence: 99%